The Influence of Halal Lifestyle, Halal Knowledge and Promotion on Rabbani Brand Purchasing Decisions: (Study on Rabbani Consumers in Medan City) - Yamin, Muhammad; Murtani, Alim (LPPPIPublishing, 2024)
This study aims to determine and analyze the influence of halal lifestyle, halal knowledge and promotion on purchasing decisions of Rabbani Brand (Study on Rabbani Consumers in Medan City). This study uses a quantitative method, with an associative approach. The number of samples in this study was 92 respondents, namely consumers of Rabbani Medan Store). The data source used in this study is primary data obtained by distributing questionnaires to respondents. Data analysis techniques in this study are data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing carried out using SPSS software version 25. The results of the study indicate that Halal Lifestyle partially has a positive and significant effect on Consumer Purchasing Decisions at Rabbani Medan Store in 2024. This is evidenced by the t-count value of 3.430 which is greater than the t-table of 1.662 and has a significant figure of 0.001 <0.05. Halal Knowledge partially influences Consumer Purchasing Decisions at Rabbani Medan Store in 2024. This is evidenced by the t-count value of 3.040 which is greater than the t-table of 1.662 and has a significant figure of 0.003 <0.05. Promotion partially influences Consumer Purchasing Decisions at Rabbani Medan Store in 2024. This is evidenced by the t-value of 2.922, which is greater than the t-table of 1.662 and has a significant figure of 0.004 <0.05. The results of the study indicate that Promotion is classified as very satisfying consumer expectations, because the promotions offered are very affordable for consumers who have a limited shopping budget. Halal Lifestyle, Halal Knowledge and Promotion simultaneously have a positive and significant effect on Consumer Purchasing Decisions at Rabbani Medan Store in 2024. This is evidenced by the F-value of 29.860, which is greater than the F-table of 2.01 and has a significant figure of 0.00 <0.05. Based on the results of the determination coefficient test (Adjust R Square), it is known that the Halal Lifestyle, Halal Knowledge and Promotion variables can explain the level of Consumer Purchasing Decisions by 48.8%. While the rest (51.2%) can be explained by other factors not examined in this study.